Engineered M2a macrophages for the treatment of osteoarthritis - Liang, Chi; Wu, Song; Xia, Guang; Huang, Junjie; Wen, Zi; Zhang, Wenxiu; Cao, Xu (Frontiers in Immunology, 2022)
Background Macrophage is a central regulator of innate immunity. Its M2 subsets, such as interstitial synovial macrophages, have been found to play critical roles in suppressing chronic inflammation and maintaining homeostasis within the joint. These macrophages have great potential as a disease-modifying cell therapy for osteoarthritis (OA). However, this has not yet been studied. Methods Macrophages were isolated from the bone marrow of rats. We constructed a stable macrophage that “locked” in anti-inflammatory and pro-regenerative M2a polarity (L-M2a) by simultaneously knocking out tumor necrosis factor receptor 1 (TNFR1) and overexpressing IL-4 using Cas9-ribonuclear proteins (Cas9-RNP) and electroporation. In vitro, these L-M2a macrophages were treated with OA synovial fluid or co-cultured with OA chondrocytes or fibroblast-like synoviocytes (FLS). In vivo, L-M2a macrophages were injected intra-articularly to evaluate their homing and engrafting abilities and therapeutic effects on OA progression using a rat model. Results L-M2a macrophages displayed a typical anti-inflammatory phenotype similar to that of M2 macrophages in vitro. In OA microenvironment, L-M2a macrophages maintained a stable anti-inflammatory phenotype, whereas unmodified M2 macrophages lost their phenotype and switched to M1 polarity. L-M2a macrophages demonstrated a potent anti-inflammatory effect in crosstalk with OA-FLSs and an anti-degenerative effect in crosstalk with senescent OA chondrocytes. In vivo, compared with M2 macrophages and exosomes, L-M2a macrophages exhibited significantly superior therapeutic effects in OA by successfully resolving inflammation, restoring tissue homeostasis, and promoting cartilage regeneration. Conclusion The engineered L-M2a macrophages maintained a superior anti-inflammatory and pro-regenerative capacity in the inflammatory OA microenvironment and represents an ideal new strategy for the disease-modifying therapy of OA.